Saudi Arabia : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper assesses the importance of oil and interest rate spillovers for Saudi Arabia. Oil prices have fallen by more than 40 percent since mid-2014 while the Federal Reserve is expected in the coming months to begin raising its policy rate at the beginning of a gradual tightening cycle. Given the importance of oil to the economy and the peg of the riyal to the U.S. dollar, these are two key developments for Saudi Arabia. Although a temporary drop in oil prices would likely have little effect on the economy and banks given the financial cushions that have been built-up, a longer-lasting period of low oil prices would have a more significant impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet